Subsidized Microfinance and Sustainability of Self-Help Groups (SHGs): Observations from North East India - Sharma, Purna Prasad; Pati, Ambika Prasad (Indian Journal of Finance, 2015)
In India, the subsidized scheme is one of the variants of microfinance introduced by the Central Government and similar subsidy based microfinance schemes have also been introduced by other donor agencies. The decadal growth of the number of subsidized SHGs and loan size under these schemes indicate the fact that SHGs are more attracted towards subsidy. However, the key question that has been asked in many research studies is about the relationship of subsidy with that of long-term sustainability of MFIs/SHGs. With the help of randomly selected 150 subsidized SHGs operating in one of the eight states of North East India, that is, Meghalaya, the study established that subsidy has negatively influenced the long-term sustainability of the SHGs. In case the subsidy is withdrawn, the SHGs would be less sustainable-operationally as well as financially. Furthermore, the withdrawal of subsidy would increase the onward lending rate manifold so as to discourage the members to take any loan from the group, thus threatening the entire program.